Figurative Language Used in Bo Burnham’s Stand-Up Comedy Titled What. - Hansel Christian Handy Junior (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study aims to find out the types of figurative language and the function of the figurative language used in Bo Burnham’s stand-up comedy titled “what.”. The writer conducted this study using the theory of types of figurative language and functions of figurative language by Harris (2018). The writer conducted the study using a qualitative approach method in which he collected and analyzed the data himself. Findings reveal that the figurative language used in